2014
DOI: 10.5713/ajas.2013.13543
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Ultrasound and Carcass Measurement Traits in a Regional Hanwoo Steer Population

Abstract: Ultrasound measurements of backfat thickness (UBF), longissimus muscle area (ULMA) and marbling score (UMS) and carcass measurements of carcass weight (CW), backfat thickness (BF), longissimus muscle area (LMA), and marbling score (MS) on 7,044 Hanwoo steers were analyzed to estimate genetic parameters. Data from Hanwoo steers that were raised, finished in Hoengseong-gun, Gangwon-do (province) and shipped to slaughter houses during the period from October 2010 to April 2013 were evaluated. Ultrasound measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
5
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
8
5
1
Order By: Relevance
“…The estimated heritability of the eight analyzed traits were moderate to high, ranging from 0.19 to 0.59 ( Table 2 ), indicating considerable additive genetic variation in most of the traits. The estimates of posterior heritability for the carcass traits were 0.56 (BFT), 0.42 (CW), 0.50 (EMA), and 0.59 (MS), which were comparable to those previously reported in Hanwoo cattle [ 15 , 17 , 18 , 19 , 20 , 21 , 22 ]. Our heritability estimate of 0.31 for YW was similar to the estimates of 0.26 and 0.30 obtained by Mehrban et al [ 21 ] and Park et al [ 15 ], respectively, but was higher than the estimate of 0.18 obtained by Choi et al [ 19 ] in Hanwoo beef cattle.…”
Section: Resultssupporting
confidence: 83%
“…The estimated heritability of the eight analyzed traits were moderate to high, ranging from 0.19 to 0.59 ( Table 2 ), indicating considerable additive genetic variation in most of the traits. The estimates of posterior heritability for the carcass traits were 0.56 (BFT), 0.42 (CW), 0.50 (EMA), and 0.59 (MS), which were comparable to those previously reported in Hanwoo cattle [ 15 , 17 , 18 , 19 , 20 , 21 , 22 ]. Our heritability estimate of 0.31 for YW was similar to the estimates of 0.26 and 0.30 obtained by Mehrban et al [ 21 ] and Park et al [ 15 ], respectively, but was higher than the estimate of 0.18 obtained by Choi et al [ 19 ] in Hanwoo beef cattle.…”
Section: Resultssupporting
confidence: 83%
“…Kim et al [51] had also reported a medium negative correlation between EMA and BFT. The genetic and phenotypic correlation estimated between MS and EMA was higher than what was reported previously by Roh et al and Son et al [48,56] but consistent with the estimates of Hwang et al [49]. These results suggest that a selection based on CWT will have a low to medium improvement in BFT, EMA, and MS, while a selection based on BFT or MS will have minimal improvement on BFT.…”
Section: Phenotypes and Genomic Heritability Estimatessupporting
confidence: 88%
“…The carcass traits of the sample were normally distributed ( Table 1). The mean values of CWT, BFT, EMA, and MS measured at a similar slaughter age were consistent with those of Roh et al [48] but differed marginally with [49]. Several previous studies have reported lower estimates for these traits [29,50], which could be attributed to differences in the number of animals investigated or nutritional status during finishing period or due to differences in the methods employed for measuring the phenotypes.…”
Section: Phenotypes and Genomic Heritability Estimatessupporting
confidence: 82%
“…and BT were very low and positive (0.18), which is corroborated by the results of earlier studies (0.17 [24]; 0.16 [11]; 0.17 [32]), but was considerably lower than the estimate of 0.40 reported by Hwang et al [33] [12,19,20,28]. However, a negative genetic correlation was observed between MS and EMA (−0.40) in an earlier study in Hanwoo cattle [11].…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 85%